The role of compliance with accounting disclosure requirements in improving the quality attributes of financial statements of economic entities in Algeria: A study of opinions of a sample of financial users in southeastern Algeria - Kouici, Mohamed (The International tax journal, 2025)
This study seeks to identify the extent of the impact of compliance with accounting disclosure requirements on the media content of financial statements issued by economic institutions in Algeria, in light of the growing need and importance of accounting information for users of financial statements in the decision-making process; A field study was conducted using a questionnaire tool, to distribute the form to a sample of users of financial statements: such as economic institutions, banks, and the tax administration in the southeast of Algeria, in order to collect and analyse data using the Statistical Package for the Social Sciences (SPSS) program; The study concluded that there is a commitment to the accounting disclosure requirements by economic institutions in Algeria after the implementation of the financial accounting system (SCF) in 2010, as it contributed positively to improving the quality of accounting information contained in the financial statements, which enhanced the media content of these statements, by increasing reliance on them and their impact on decision-makers.